2013
DOI: 10.20886/jpht.2013.10.3.119-127
|View full text |Cite
|
Sign up to set email alerts
|

EVALUASI PERTUMBUHAN AWAL JABON (Neolamarckia cadamba Roxb) DI HUTAN RAKYAT

Abstract: Neolamarckia cadamba Neolamarckia cadamba Jabon merupakan salah satu jenis pohon cepat tumbuh, sehingga jabon sangat diminati untuk dikembangkan di hutan rakyat dan hutan tanaman industri. Namun, pertumbuhan yang optimal akan tercapai jika pemahaman tentang teknik silvikultur seperti manajemen hara di tapak sangat dibutuhkan. Selain itu, luas lahan milik yang diperuntukkan untuk membangun hutan rakyat tidak terlalu luas, sementara kebutuhan untuk budidaya tanaman hortikultura juga penting. Untuk itu penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
1
0
5
Order By: Relevance
“…The distribution (%) of jabon height in some classes at 6, 12 and 24 MaP species, the growth of jabon in DP was poor. As fast-growing species, some previous studies showed that the height and DBH increments of jabon at 2-4 years in dryland could reach 1.62-4.21 m/year and 2.03-5.25 cm/year (Abdulah, Mindawati, Kosasih, & Darwo, 2013;Bijalwan, Dobriyal, & Bhartiya, 2014a;Seo, Chun, Mansur, & Lee, 2015;Wahyudi, 2012;Zuhaidi, Hashim, Sarifah, & Norhazaedawati, 2012;Zuhaidi, 2013). It means that the height and DBH of jabon in optimal growth in DP could reach 3.24-8.42 m and 4.06-10.50 cm at the age of 24 MaP, but in this study, it was 2.59 m and 3.74 cm, respectively.…”
Section: A the Survival Rate Growth And Spacing Effectmentioning
confidence: 99%
“…The distribution (%) of jabon height in some classes at 6, 12 and 24 MaP species, the growth of jabon in DP was poor. As fast-growing species, some previous studies showed that the height and DBH increments of jabon at 2-4 years in dryland could reach 1.62-4.21 m/year and 2.03-5.25 cm/year (Abdulah, Mindawati, Kosasih, & Darwo, 2013;Bijalwan, Dobriyal, & Bhartiya, 2014a;Seo, Chun, Mansur, & Lee, 2015;Wahyudi, 2012;Zuhaidi, Hashim, Sarifah, & Norhazaedawati, 2012;Zuhaidi, 2013). It means that the height and DBH of jabon in optimal growth in DP could reach 3.24-8.42 m and 4.06-10.50 cm at the age of 24 MaP, but in this study, it was 2.59 m and 3.74 cm, respectively.…”
Section: A the Survival Rate Growth And Spacing Effectmentioning
confidence: 99%
“…Beberapa penelitan telah menunjukkan bahwa riap tinggi dan diameter jabon pada rentang umur 2 -4 tahun dapat mencapai 1,62 -4,21 m/tahun dan 2,03 -5,25 cm/tahun (Abdulah, Mindawati, & Kosasih, 2013;Bijalwan, Dobriyal, & Bhartiya, 2014;Seo, Kim, Chun, Mansur, & Lee, 2015;Bastoni 2002dalam Siahaan & Rahman, 2007Wahyudi, 2012;Zuhaidi, 2013;Zuhaidi, Hashim, Sarifah, & Norhazaedawati, 2012).…”
Section: Pertumbuhan Tanaman Bunclassified
“…Bentuk batang jabon adalah lurus dan silindris. Jabon ditemukan tumbuh secara alami di wilayah Sulawesi Bagian Utara, dan Maluku (Abdulah, et al, 2013). Jabon merupakan jenis pohon dari famili Rubiaceae yang memiliki banyak kegunaan.…”
Section: Pendahuluanunclassified